CIDOS integration in design process for producing creative product - Isham Shah Hassan; Zainal Azhar Zainal Abidin; Azlin Ismail Effendi (Proceedings of AICS - Social Sciences, 2013)
The purpose of this research is to examine the effect of integrating CiDOS on teaching architectural design process for Malaysian polytechnic architectural students in producing a creative product. The web based information is set up based on Caroll’s minimal theory, while the integration is based on Brown and Campione’s technology of learning theory. This study utilized a quasi-experimental method. Final semester students from two (2) classes being used as research samples where sixty (25) students are in the treatment group and another sixty (25) students are in the control group. The final products being evaluated by the experts in architectural field using an instrument based on Creative Product Analysis Model (CPAM). The inferential statistics namely T-Test and Pearson Correlation Analysis with a significant level p = 0.01 were utilized. Research outcome shows that there is a significant difference between the treatment group product (M=79.1) and control group product (M=70.5).  This research contributes to the use of real case in the development of an architectural website, in the use of mobile technology as media information sources and in the construction of validated instrument which is used to evaluate creative architectural products.Keywords: Web Mobile, Design Process, Creative Product, CPAM